Mediation of exogenous hydrogen sulfide in recovery of ischemic post-conditioning-induced cardioprotection via down-regulating oxidative stress and up-regulating PI3K/Akt/GSK-3β pathway in isolated aging rat hearts - Hongzhu Li; Yuehong Wang; Can Wei; Shuzhi Bai; Yajun Zhao; Hongxia Li; Bo Wu; Rui Wang; Lingyun Wu; Changqing Xu (2015)
The physiological and pathological roles of hydrogen sulfide (H2S) in the regulation of cardiovascular functions have been recognized. Cystathionine gamma-lyase (CSE) is a major H2S-producing enzyme in cardiovascular system. Ischemic post-conditioning (PC) provides cadioprotection in young hearts but lost in the aging hearts. The involvement of H2S in the recovery of PC-induced cardioprotection in the aging hearts is unclear. In the present study, we demonstrated that ischemia/reperfusion (I/R) decreased H2S production rate and CSE expression, aggravated cardiomyocytes damage, apoptosis and myocardial infarct size, reduced cardiac function, increased the levels of Bcl-2, caspase-3 and caspase-9 mRNA, enhanced oxidative stress in isolated young and aging rat hearts. I/R also increased the release of cytochrome c and down-regulated the phosphorylation of PI3K, Akt and GSK-3β in the aging rat hearts. We further found that PC increased H2S production rate and CSE expressions, and protected young hearts from I/R-induced cardiomyocytes damage, all of which were disappeared in the aging hearts. Supply of NaHS not only increased PC-induced cardioprotection in the young hearts, but also lightened I/R induced-myocardial damage and significantly recovered the cardioprotective role of PC against I/R induced myocardial damage in the aging hearts. LY294002 (a PI3K inhibitor) abolished but N-acetyl-cysteine (NAC, an inhibitor of reactive oxygen species, ROS) further enhanced the protective role of H2S against I/R induced myocardial damage in the aging hearts. In conclusion, these results demonstrate that exogenous H2S recovers PC-induced cardioprotection via inhibition of oxidative stress and up-regulation of PI3K-Akt-GSK-3β pathway in the aging rat hearts. These findings suggested that H2S might be a novel target for the treatment of aging cardiovascular diseases.